Kritik Nalar Filsafat Ketuhanan Versi Islam Dan Barat (Kajian Pemikiran Ibn Rusyd Dan Alfred North Whitehead) - suhandi, suhandi; Azis, Abdul; Musofa, Ade (AL-ADYAN, 2023)
This article is a study of divine philosophy that more specifically discusses the concept of divinity by Ibn Rushd and Alfred North Whitehead. The method used consists of two stages: concept formation (tashawur) and logical reasoning (tashdiq). Ibn Rushd's epistemological thinking contains certain implications and consequences. First, Ibn Ruyd's concept of two sources of knowledge can encourage a meeting between religion and science, as well as religion and philosophy, but on the other hand it can also give birth to materialistic, secular and even atheistic thoughts, at least the doctrine of "double truths" as happened in Europe in medieval ages. This means that this problem must be watched out for and paid attention to. Alfred North Whitehead's concept of Divinity, is that of God, humans, animals, plants, and inanimate objects. The universal principle is the principle of "process". This principle assumes that every being is essentially determined by how he then appears in the process of becoming himself, reality is not something static, but continues to move and change in an unending process of evolution.